Solve each system of equations. If possible, write your answer as an ordered pair.
x + 5y = 11
x + y = 3

Rating

3

x + 5y = 11

x + y = 3

The first equation - the second equation: 4y = 8, y = 2

x + 5(2) = 11

x = 11 - 10 = 1

The solution for the system of equations: x + 5y = 11, x + y = 3 is (1, 2)

x + y = 3

The first equation - the second equation: 4y = 8, y = 2

x + 5(2) = 11

x = 11 - 10 = 1

The solution for the system of equations: x + 5y = 11, x + y = 3 is (1, 2)

Added 4/9/2014 7:02:57 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/9/2014 7:07:55 PM]

Carlos has $3.35 in dimes and quarters. If he has a total of 23 coins, how many dimes does he have?
a
9
b
11
c
16
d
18

Question|Asked by kd142927

Updated 4/9/2014 8:13:29 PM

1 Answer/Comment

Solve each system of equations. If possible, write your answer as an ordered pair.
y = -3x + 2
y = 4x - 5
**Weegy:** 4x + 12 = -3x - 6 + 4x, 4x + 12 = x - 6, 12 + 6 = x - 4x, 18 = -3x or -3x = 18, x = -6 (More)

Question|Asked by kd142927

Updated 4/9/2014 8:06:24 PM

1 Answer/Comment

y = -3x + 2

y = 4x - 5

replace y in the first equation we get:

4x - 5 = -3x + 2

4x + 3x = 2 + 5

7x = 7

x = 1

y = 4(1) - 5 = -1

The solution for the system of equations y = -3x + 2 y = 4x - 5 is (1, -1)

y = 4x - 5

replace y in the first equation we get:

4x - 5 = -3x + 2

4x + 3x = 2 + 5

7x = 7

x = 1

y = 4(1) - 5 = -1

The solution for the system of equations y = -3x + 2 y = 4x - 5 is (1, -1)

Added 4/9/2014 8:06:24 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/9/2014 8:06:50 PM]

Solve each system of equations. If possible, write your answer as an ordered pair.
y = 5x - 3
y = 2x + 6

Question|Asked by kd142927

Updated 4/9/2014 8:04:27 PM

1 Answer/Comment

y = 5x - 3

y = 2x + 6

replace y in the first equation we get:

2x + 6 = 5x - 3

2x - 5x = -3 - 6

-3x = -9

x = 3

y = 5(3) - 3 = 15 - 3 = 12

The solution for the system of equations y = 5x - 3 y = 2x + 6 is (3, 12)

y = 2x + 6

replace y in the first equation we get:

2x + 6 = 5x - 3

2x - 5x = -3 - 6

-3x = -9

x = 3

y = 5(3) - 3 = 15 - 3 = 12

The solution for the system of equations y = 5x - 3 y = 2x + 6 is (3, 12)

Added 4/9/2014 8:04:27 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/9/2014 8:08:11 PM]

Solve each system of equations. If possible, write your answer as an ordered pair.
x + y = 8
x + 3y = 14
**Weegy:** 1 x - 3 y = - 6 ? y = x 3 + 2 (More)

Question|Asked by kd142927

Updated 4/9/2014 7:52:39 PM

1 Answer/Comment

x + y = 8

x + 3y = 14

the first equation - the second equation: 2y = 6

solve the equation: y = 3

x + 3 = 8, x = 5

The solution for the system of equations x + y = 8, x + 3y = 14 is (5, 3)

x + 3y = 14

the first equation - the second equation: 2y = 6

solve the equation: y = 3

x + 3 = 8, x = 5

The solution for the system of equations x + y = 8, x + 3y = 14 is (5, 3)

Added 4/9/2014 7:52:39 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/9/2014 8:06:37 PM]

Solve each system of equations. If possible, write your answer as an ordered pair.
y = -2x + 6
y = 3x - 9
**Weegy:** x = 2.5 (More)

Question|Asked by kd142927

Updated 4/9/2014 7:55:11 PM

1 Answer/Comment

y = -2x + 6

y = 3x - 9

Replace y in the first equation:

3x - 9 = -2x + 6

5x = 15,

x = 3

y = -2(3) + 6 = 0

The solution for the system of equations y = -2x + 6 y = 3x - 9 is (3, 0)

y = 3x - 9

Replace y in the first equation:

3x - 9 = -2x + 6

5x = 15,

x = 3

y = -2(3) + 6 = 0

The solution for the system of equations y = -2x + 6 y = 3x - 9 is (3, 0)

Added 4/9/2014 7:55:11 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/9/2014 8:02:39 PM]

32,282,109

questions answered

There are no comments.